Foodborne doping and supervision in sports - Wei Chen; Xiaoyu Cheng; Yingnan Ma; Ning Chen (Food Science and Human Wellness)
Cases of foodborne doping are frequently reported in sports events and can cause severe consequences for athletes. The foodborne doping can be divided into natural endogenous and artificially added foods according to the sources, including anabolic agents, stimulants, diuretics, β-blockers, β2 agonists and others. In order to control foodborne doping, chromatographic technique, immunoassay, nuclear magnetic resonance, biosensor technology, pyrolytic spectroscopy, comprehensive analysis and electrochemical analysis have usually used as analytical and inspection strategies. Meanwhile, the legislation of anti-doping, the improvement of testing standard and technology, and the prevention and control of food safety, as well as the improvement of risk perception of athletes are highly necessary for achieving the effective risk control and supervision of foodborne doping, which will be beneficial for athletes, doctors and administrators to avoid the risks of foodborne doping test and reduce foodborne doping risks for the health of athletes.